2007
DOI: 10.1086/511383
|View full text |Cite
|
Sign up to set email alerts
|

H2O Maser Observations of Candidate Post‐AGB Stars and Discovery of Three High‐Velocity Water Sources

Abstract: We present the results of 22 GHz H 2 O maser observations of a sample of 85 postYasymptotic giant branch ( post-AGB) candidate stars, selected on the basis of their OH 1612 MHz maser and far-infrared properties. All sources were observed with the Tidbinbilla 70 m radio telescope, and 21 detections were made; 86 GHz SiO Mopra observations of a subset of the sample are also presented. Of the 21 H 2 O detections, 15 are from sources that are likely to be massive AGB stars and most of these show typical, regular H… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
106
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(114 citation statements)
references
References 76 publications
(169 reference statements)
8
106
0
Order By: Relevance
“…Besides the detection of 321 GHz H 2 O maser emission (Tafoya et al 2014), Pérez-Sánchez et al (2011), Walsh et al (2009 also reported the detection of the 22 GHz H 2 O maser transition. In most cases the bandwidth used for the observations led to the detection of maser spectral features over velocity ranges > 300 km s −1 , a fact that confirmed the results reported by Deacon et al (2007).…”
Section: Iras 18043-2116supporting
confidence: 82%
See 1 more Smart Citation
“…Besides the detection of 321 GHz H 2 O maser emission (Tafoya et al 2014), Pérez-Sánchez et al (2011), Walsh et al (2009 also reported the detection of the 22 GHz H 2 O maser transition. In most cases the bandwidth used for the observations led to the detection of maser spectral features over velocity ranges > 300 km s −1 , a fact that confirmed the results reported by Deacon et al (2007).…”
Section: Iras 18043-2116supporting
confidence: 82%
“…Therefore, from the velocity of the 1665 MHz OH maser spectral features, the authors suggested a radial velocity for the stellar source of 87.5 km s −1 . Deacon et al (2007) reported the detection of high-velocity 22 GHz H 2 O maser emission, with spectral features having velocities outside the velocity range defined by the double-peaked 1665 MHz OH maser spectrum (∆v= v red −v blue ≈ 33 km s −1 , Deacon et al 2004). This led the authors to classify the source as a Water Fountain nebulae.…”
Section: Iras 18043-2116mentioning
confidence: 99%
“…It did not exhibit significant variability between the two epochs of our observations. In this source, the 22 GHz maser emission reported by Deacon et al (2007) and Pérez-Sánchez et al (2011) appears over the velocity range from ∼−150 km s −1 to ∼−75 km s −1 . In addition, the OH maser emission consists of a broad spectral feature that covers the velocity range from ∼−200 km s −1 to ∼−110 km s −1 (Deacon et al 2007).…”
Section: Iras 15445−5449mentioning
confidence: 64%
“…In this source, the 22 GHz maser emission reported by Deacon et al (2007) and Pérez-Sánchez et al (2011) appears over the velocity range from ∼−150 km s −1 to ∼−75 km s −1 . In addition, the OH maser emission consists of a broad spectral feature that covers the velocity range from ∼−200 km s −1 to ∼−110 km s −1 (Deacon et al 2007). Thus, the 321 GHz H 2 O maser emission has a velocity range in better agreement with the range of the OH maser emission do the 22 GHz water masers.…”
Section: Iras 15445−5449mentioning
confidence: 64%
See 1 more Smart Citation